Meningkatkan Aktivitas Dan Hasil Belajar Muatan IPA Menggunakan Model PBL Dan NHT Di SDN Hapingin - Muhammad Ali Fikri; Sunarno (Jurnal Pendidikan Sosial Dan Konseling, 2024)
The problem of this research is low activity, students are less involved in learning and student learning outcomes in class IV SDN Hapingin Hulu Sungai Tengah with a total of 10 students. The purpose of this study was to describe teacher activities, analyze student activities, and learning outcomes in carrying out learning in science content with the PBL and NHT models. This study used the type of Classroom Action Research which was conducted in 4 meetings. Data were analyzed based on observations of teacher activities, student activities, and student learning outcomes using descriptive techniques, described in tables and graphs. The results of this study showed that there was an increase in teacher activity which at first meeting only got a score of 21 with a percentage of 65.6% and increased at meeting 4 with a score of 30 with a percentage of 94.75%. In classical student activity also experienced an increase, it can be seen from the percentage which was initially 50% then experienced an increase in meeting 4 which increased by a percentage of 100%. In student learning outcomes from meeting 1 with a percentage of 60% students have completed then at meeting 4 it has increased to 100% students complete.